Use the OPAC: education service users for use of automated catalogs - Paz Enrique, Luis Ernesto (2015)
Service design and information products must be based on the information needs of users. Education services for users seeking to build skills in users for their efforts before the search, retrieval and use of information. The research presented classified as applied, it provides solutions to problems identified in practice. To obtain results methods are combined in the theoretical and empirical level, as well as techniques that facilitate the collection of information. Is designed an education service users for the use of automated catalogs, resulting in the design of a tutorial for users of the Centre for Scientific and Technical Information Documentation of the Universidad Central “Marta Abreu” de Las Villas. For service design takes into account aspects such as the context, users and human, political and financial limitations